Effect of magnesia-alumina spinel precursor sol on the sintering property of fused magnesia refractory. Issue 3 (15th February 2019) - Hou, Qingdong; Luo, Xudong; Xie, Zhipeng; An, Di; Zhang, Xiaofang; Peng, Zijun
Abstract: The sintering property of fused magnesia refractory was investigated by the fused magnesia powder as matrix and the synthetic magnesia-alumina spinel precursor sol as binder. The spinel precursor sol was prepared by co-precipitation method and was characterized by its particle size, thermal analysis, microstructure, phase development with temperatures, and so on. The effect of spinel precursor sol on the sintering property of fused magnesia refractory were studied after heat treatment at 1450 °C and 1550 °C. The results showed that the bulk density, flexural strength and linear shrinkage of the sintered samples firstly increase and then decrease with increasing spinel precursor sol. The bulk density and flexural strength (cold modulus of rupture) of the sample sintered at 1550 °C, introduced with 1 wt% spinel precursor sol, reached 3.10 g/cm 3 and 47.25 MPa, respectively. From the experimental results, magnesia-alumina spinel precursor sol can replace the traditional binders and improve the sintering property of fused magnesia products.